1995
DOI: 10.1103/physrevb.52.3555
|View full text |Cite
|
Sign up to set email alerts
|

Surface and bulk magnetic properties of pyriteNiS2: Magnetization and neutron-scattering studies

Abstract: In pyrite-structure antiferromagnetic NiS2, the magnetic susceptibility y(T) shows downward curvature above the Neel transition (T~i --39.2 K), suggesting that magnetic correlations persist to T = 400 K. However, neutron-scattering measurements indicate that the bulk magnetic behavior above Typal is conventional. We present evidence that the unusual temperature dependence of y(T) arises from a surface contribution. At T~2 --29.75 K a transition occurs to a weakly ferromagnetic state, accompanied by a small str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 17 publications
2
29
0
Order By: Relevance
“…Transition metal sulfides such as copper sulfides [2,3], ferric sulfides [4,5], cobalt sulfides [6e8] and nickel sulfides [9e13] have been actively investigated as possible candidates for anode materials due to their high capacity, low cost and eco-friendliness. Among the family of transition metal sulfides, nickel sulfides have caused a special attention due to their interesting electronic, magnetic, optical properties [14,15] and their multiple potential applications including LIBs [9e13], supercapacitors [16e18] and catalysts [19,20]. It was reported that the various phases of nickel sulfides such as NiS [9], Ni 3 S 2 [10,11], Ni 3 S 4 [12], Ni 7 S 6 [13] exhibited higher specific capacity as anode materials of LIBs compared to graphite anode material.…”
Section: Introductionsmentioning
confidence: 99%
“…Transition metal sulfides such as copper sulfides [2,3], ferric sulfides [4,5], cobalt sulfides [6e8] and nickel sulfides [9e13] have been actively investigated as possible candidates for anode materials due to their high capacity, low cost and eco-friendliness. Among the family of transition metal sulfides, nickel sulfides have caused a special attention due to their interesting electronic, magnetic, optical properties [14,15] and their multiple potential applications including LIBs [9e13], supercapacitors [16e18] and catalysts [19,20]. It was reported that the various phases of nickel sulfides such as NiS [9], Ni 3 S 2 [10,11], Ni 3 S 4 [12], Ni 7 S 6 [13] exhibited higher specific capacity as anode materials of LIBs compared to graphite anode material.…”
Section: Introductionsmentioning
confidence: 99%
“…The magnetostrictive response of the lattice to M2 is likely rhombohedral 19 and the distortion from cubic symmetry is extremely small, with a relative lattice constant change ∆a/a ∼ 2 × 10 −4 (Ref. [20]).…”
Section: Antiferromagnetism At Ambient and High Pressuresmentioning
confidence: 99%
“…At T N 2 the type II AF structure appears in addition to the type I structure. This is accompanied by the rhombohedral distortion and with the mysterious WF [21]. This lattice distortion (d > 0) lifts the quasidegeneracy of type I and type II structures [30].…”
Section: Shown Inmentioning
confidence: 99%
“…Experimentally anomalous behaviors in the fcc AF are often observed. For example there occurs mysterious weak ferromagnetism (WF) in NiS 2 below the second AF transition temperature T N 2 [21]. The Hall effect in this material is also large and strongly temperature dependent [22].…”
mentioning
confidence: 99%